THE LEGAL RELATIONSHIP STATUS OF LOADING AND UNLOADING AFTER THE JOB CREATION LAW - Asri Wijayanti (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2023)
The status of stevedoring labor legal relations is still debated among labor law experts. As a permanent worker, outsourcer, daysman, or no employment relationship. Focus the study to analyze the status of the legal relationship between stevedoring workers and the legal consequences, along with legal remedies that can be taken by stevedoring workers, if they have not received maximum rights. The case and statutory approaches are used in this legal research. The results of the research study after analysis of the substance and procedure are the status of legal relations of stevedoring labor, more precisely as daily workers, and as members of cooperatives. The legal consequence of the employment relationship status of stevedoring workers with cooperatives is the right to share the remaining operating results, at the end of the year. The legal consequence of the loading and unloading labor service work is wages based on daily time units. There is no right to severance pay, service award money, or reimbursement money because it is not stipulated in the Cooperative Annual Member Meeting. Legal actions that can be taken by stevedoring workers if they do not get their rights can file a default lawsuit in the local District Court. The recommendation given is that cooperatives can establish additional rights for bonfire loading workers, such as rights that should obtain permanent employment, through the annual meeting of cooperative members. Abstrak: Status hubungan hukum tenaga kerja bongkar muat, sampai sekarang masih menjadi perdebatan di kalangan ahli hukum ketenagakerjaan. Sebagai pekerja tetap, pekerja alih daya, pekerja harian, atau tidak ada hubungan kerja. Penelitian ini bertujuan untuk menganalisis status hubungan hukum tenaga kerja bongkar muat dan akibat hukum, beserta upaya hukum yang dapat dilakukan oleh tenaga kerja bongkar muat, apabila belum mendapat hak secara maksimal. Penelitian hukum ini menggunakan pendekatan perundang undangan dan kasus. Hasil penelitian setelah dilakukan analisis substansi dan prosedur adalah status hubungan hukum tenaga kerja bongkar muat, lebih tepat sebagai pekerja harian, dan sebagai anggota koperasi. Akibat hukum atas status hubungan kerja tenaga kerja bongkar muat dengan koperasi adalah adanya hak atas pembagian sisa hasil usaha, di akhir tahun. Akibat hukum atas telah dijalankannya pekerjaan jasa tenaga kerja bongkar muat adalah upah berdasar satuan waktu harian. Tidak ada hak atas uang pesangon, uang penghargaan masa kerja dan uang penggantian hak, karena tidak ditetapkan dalam Rapat Anggota Tahunan Koperasi. Upaya hukum yang dapat dilakukan oleh tenaga kerja bongkar muat apabila tidak mendapatkan haknya dapat mengajukan gugatan wanprestasi di Pengadilan Negeri setempat. Rekomendasi yang diberikan adalah koperasi dapat menetapkan tambahan hak bagi tenaga kerja bongkar muat, seperti hak yang seharusnya diperoleh pekerjaan tetap, melalui rapat tahunan anggota koperasi. Kata Kunci: Tenaga Kerja Bongkar Muat, Pekerja Harian, Koperasi, Hubungan Kerja.